2023
DOI: 10.3390/electronics12071612
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Digitalization on Macroeconomic Indicators in the New Industrial Age

Abstract: Digitalization has become a watchword in all areas of economic and social activity, and its integration has become a necessity for every state worldwide. If a few years ago we were talking about technological innovation and cutting-edge technologies we are now talking about digital technologies, robotics, big data, and artificial intelligence, and future industrial production will develop in symbiosis with modern information and communication technology. The paper aims to show the impact of digitalization on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…According to the mainstream approach, the researchers applied a digital transformation to the digitization transition experienced in company processes. However, parallel to the significant macroeconomic effects of Industry 4.0, the terminology can also be applied to the entire macroeconomics of [11,12].…”
Section: The Role and Importance Of Digital Transitionmentioning
confidence: 99%
“…According to the mainstream approach, the researchers applied a digital transformation to the digitization transition experienced in company processes. However, parallel to the significant macroeconomic effects of Industry 4.0, the terminology can also be applied to the entire macroeconomics of [11,12].…”
Section: The Role and Importance Of Digital Transitionmentioning
confidence: 99%
“…Numerous scientific studies have been conducted in this domain, with mixed findings. For example, Chenic et al (2023) empirically examined the influence of digitalization on macroeconomic variables and concluded that digitalization has a beneficial effect on GDP and value-added but has a weak correlation between digitalization and export. The authors Debbarma et al (2022) advocate in the same vein that the higher digitization of firms will have a significant positive influence on the promotion of exports.…”
Section: Variables and Development Of Hypothesismentioning
confidence: 99%
“…As a result, in compliance with this principle of testing, our study employed the Hausman analysis, the outcomes of which are shown in Table 4 in the second section titled screening tests. Our study will adopt the methodology employed by Chenic et al (2023), Wang and Choi (2019), and Bahrini and Qaffas ( 2019), but with an update to modify it to our selected variables.…”
Section: Model Developmentmentioning
confidence: 99%
“…According to the mainstream approach, digital transformation has been applied by researchers to the digital transformation of business processes. Still, the terminology can also be used for the macroeconomy as a whole, in parallel to the macroeconomic impact of Industry 4.0 [3,4].…”
Section: Introductionmentioning
confidence: 99%